HIV and pericardial fat are associated with abnormal cardiac structure and function among Ugandans. Issue 2 (19th September 2019) - Buggey, Jonathan; Yun, Leo; Hung, Chung-Lieh; Kityo, Cissy; Mirembe, Grace; Erem, Geoffrey; Truong, Tiffany; Ssinabulya, Isaac; Tang, W H Wilson; Hoit, Brian D; McComsey, Grace A; Longenecker, Chris T
Abstract : Objectives: To examine the relationship between pericardial fat (PCF) and cardiac structure and function among HIV-infected patients in the sub-Saharan African country of Uganda. People living with HIV (PLHIV) have altered fat distribution and an elevated risk for heart failure. Whether altered quantity and radiodensity of fat surrounding the heart relates to cardiac dysfunction in this population is unknown. Methods: One hundred HIV-positive Ugandans on antiretroviral therapy were compared with 100 age and sex-matched HIV-negative Ugandans; all were >45 years old with >1 cardiovascular disease risk factor. Subjects underwent ECG-gated non-contrast cardiac CT and transthoracic echocardiography with speckle tracking strain imaging. Multivariable linear and logistic regression models were used to explore the association of PCF with echocardiographic outcomes. Results: Median age was 55% and 62% were female. Compared with uninfected controls, PLHIV had lower body mass index (27 vs 30, p=0.02) and less diabetes (26% vs 45%, p=0.005). Median left ventricular (LV) ejection fraction was 67%. In models adjusted for traditional risk factors, HIV was associated with 10.3 g/m 2 higher LV mass index (LVMI) (95% CI 3.22 to 17.4; p=0.005), 0.87% worse LV global longitudinal strain (GLS) (95% CI −1.66 to −0.07; p=0.03) and higher odds of diastolic dysfunction (OR 1.96; 95% CI 0.95 to 4.06; p=0.07). In adjusted models, PCF volume was significantly associated with increased LVMI and worse LV GLS, while PCF radiodensity was associated with worse LV GLS (all p<0.05). Conclusions: In Uganda, HIV infection, PCF volume and density are associated with abnormal cardiac structure and function.